Atomic Structure and Chemical Elements (Islamic Perspective) Book as a Learning Resource - Siska Oktapianti (PT. Sharia Journal and Education Center, 2024)
This research is a detailed examination of the development of the chemistry educational sources. The aims of the research are to describe (1) the validity of teaching material (2) the students' responses to the teaching material developed. The type of research is research and development (R&D), with model 4D by Thiagarajan. The stages development of 4D are define, design, develop and desseminate. The subjects of this study are students and lecturers of UIN Antasari. The data collection techniques and instruments used in this study are interview guides, questionnaires and observations. Based on the results of expert validation: validation of material experts with an average of 81% with the criteria